“HYPERTEXT” IN ANCIENT CHINA - Wei, Yong-Kang (European Scientific Journal, ESJ, 2015)
Classical Chinese texts, written (mostly) on bamboo strips, have some features that are generally attributed to the uniqueness of modern electronic hypertext, such as non-linear, open-ended, multiaccentual, interactive, and networked. Hence the term “bamboo hypertext.” Underlying those textual features is the collective workmanship characteristic of text production in ancient China. For example, Lao Zi’s Dao De Jing and Confucius’ Lun Yu (Analects) are actually compilations of writings produced and reproduced by generations of disciples over a span of decades or even centuries. While the texts bore the name of Lao Zi or Confucius as its official author, the master himself may never have contributed a single written word to the collection. In short, individual authorship/ownership of the text is basically a non-issue when it comes to the notion of collective workmanship embodied in bamboo hypertext. Bamboo hypertext also fits into a rhetorical tradition that operates on a different philosophical basis. The fluidity of classical Chinese rhetoric is made possible by the fluidity of production and transformation of bamboo texts, as the latter imposes no physical limits on the motion of rhetoric. On the other hand, bamboo hypertext thrives also because of the openended, anti-logical nature of classical Chinese rhetoric, which, without suffering damages to textual “integrity,” permits—and sustains—fragmentation, continual transformation of text, reader/writer interaction, disruption of textual sequence, etc., features typically associated with the modern-day hypertext.